Cassava varietal response to fertilization: Growth dynamics and implications for cropping sustainability - Pellet, D; El-Sharkawy, Mabrouk A. (Cambridge University Press, 1997)
Four contrasting varieties of cassava (Manihot esculenta Crantz) were grown for ten months over two consecutive seasons in hillside Colombia with or without nitrogen, phosphorus and potassium fertilization. Sequential harvests were every two months. The two varieties well adapted to acid soils (CM 489-1 and CM 523-7) had higher yields and exhibited the strongest response to fertilization, highest solar radiation use efficiency, earlier canopy ground cover and higher leaf litter accumulation. The export of potassium, however, was no higher than in the other genotypes, mainly as a consequence of higher potassium use efficiency in the adapted varieties. Significant amounts of total calcium, magnesium and nitrogen accumulated in the whole plant were recycled in the leaf litter during growth. High-yielding varieties adapted to acid soils did not exacerbate soil fertility problems of cassava crops; rather, they were beneficial. Certain growth parameters could be used to select for varieties with low impact on soil fertility.